Sustained shift in the morphology of organic-walled microfossils over the Ediacaran–Cambrian transition - Kelly E. Tingle; Ross P. Anderson; Neil P. Kelley; Simon A. F. Darroch (Royal Society Open Science)
The early (approx. 1650–540 Ma) history of eukaryotes was punctuated by several major—but enigmatic—environmental perturbations that potentially influenced the evolution of the Proterozoic biosphere, and the changing structure of Earth systems leading up to the Cambrian Explosion of animals. Reconstructing the manner in which eukaryotes responded to these events represents an innovative lens with which to understand what these perturbations actually represent, as well as the links between geosphere and biosphere during a critical period in eukaryotic evolution. In this study, we analyse organic-walled microfossil size and morphology across the Ediacaran–Cambrian transition. We illustrate that the decrease in vesicle diameter—previously shown to occur across the Ediacaran–Cambrian transition—began in the Ediacaran following the ‘Shuram’ carbon isotope excursion. This size decrease was accompanied by an increase in relative process length across the Ediacaran–Cambrian transition, which has not been previously quantified. Finally, following the ‘Shuram’ excursion, we illustrate a sustained shift in overall morphology. This shift in morphology may have been driven by nutrient stress enhanced by environmental change and/or the increased importance of planktonic lifestyles, highlighting the expansion of microbial eukaryotes into the plankton as a key step in the establishment of modern marine food webs.